2 / ___\ asin (x) (3*x - 4)*cos\\/ x / - E
(3*x - 4)*cos(sqrt(x)) - E^(asin(x)^2)
2 asin (x) / ___\ / ___\ 2*asin(x)*e (3*x - 4)*sin\\/ x / 3*cos\\/ x / - ------------------- - -------------------- ________ ___ / 2 2*\/ x \/ 1 - x
2 2 2 / ___\ asin (x) 2 asin (x) / ___\ / ___\ asin (x) 3*sin\\/ x / 2*e 4*asin (x)*e (-4 + 3*x)*cos\\/ x / (-4 + 3*x)*sin\\/ x / 2*x*asin(x)*e - ------------ + ----------- + -------------------- - --------------------- + --------------------- - --------------------- ___ 2 2 4*x 3/2 3/2 \/ x -1 + x -1 + x 4*x / 2\ \1 - x /
2 2 2 2 2 / ___\ / ___\ asin (x) 3 asin (x) asin (x) / ___\ / ___\ / ___\ 2 asin (x) 2 asin (x) 9*cos\\/ x / 9*sin\\/ x / 14*asin(x)*e 8*asin (x)*e 6*x*e 3*(-4 + 3*x)*sin\\/ x / (-4 + 3*x)*sin\\/ x / 3*(-4 + 3*x)*cos\\/ x / 12*x*asin (x)*e 6*x *asin(x)*e - ------------ + ------------ - -------------------- - -------------------- - ------------- - ----------------------- + --------------------- + ----------------------- - ----------------------- - ---------------------- 4*x 3/2 3/2 3/2 2 5/2 3/2 2 2 5/2 4*x / 2\ / 2\ / 2\ 8*x 8*x 8*x / 2\ / 2\ \1 - x / \1 - x / \-1 + x / \-1 + x / \1 - x /